Overview of Perinatal Palliative Care in Brazil - Saffi Junior,Mario Cezar (2022)
Abstract Significant attention to palliative care in terminally ill patients has only been effective in Brazil since the year 2000, although there have been isolated actions since the 1980s. When the case involves fetuses or neonates unable to cure, communication and care with the family members only received attention and effective organization starting in 2017. Notably in the years 2015 and 2016 there was an epidemic of microcephaly and along with the persistent crisis of drug users has raised the indices of malformations to a level higher than 3 % of the world average. Here we aim the evaluation of: a) social, educational and spiritual profile of the mothers; b) structure of the specific teams related to palliative care in neonatology; c) recommendations and protocols currently used in the country. The method used is an electronic retrospective on databases and government data; evaluation of the location and composition of palliative care teams in the country. The data found clearly point out that for Brazilian women, the characteristics of regionality in the country, educational level, religiousness and quality of life directly influence pregnancy and the acceptance or not of the possibility of death, directly influencing perinatal palliative care, which, by the way, is still developing methodologies for this type of action.